2015
DOI: 10.1097/mco.0000000000000177
|View full text |Cite
|
Sign up to set email alerts
|

Developmental programming of type 2 diabetes

Abstract: Epigenetic processes may represent a central underlying mechanism of developmental programming of type 2 diabetes. During embryonic and foetal development, extensive epigenetic remodelling takes place not only in somatic but also in primordial germ cells. Therefore, concerns have been raised that epigenetic dysregulation induced by a suboptimal early environment could programme altered phenotypes not only in the first generation but also in the subsequent ones. Characterizing these altered epigenetic marks has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…In many recent studies, compelling evidence was provided that changes in epigenetic regulation of gene expression (heritable alterations in gene function without changes in the nucleotide sequence) is the most plausible mechanism for the link between unfavourable conditions in early development and adverse health outcomes in later life [20]. The main epigenetic mechanisms are DNA methylation and post-translational modifications of histone tails, as well as regulation by non-coding RNAs (microRNAs and long non-coding RNAs) [21].…”
Section: Conceptual Framework For Developmental Nutritional Programentioning
confidence: 99%
See 1 more Smart Citation
“…In many recent studies, compelling evidence was provided that changes in epigenetic regulation of gene expression (heritable alterations in gene function without changes in the nucleotide sequence) is the most plausible mechanism for the link between unfavourable conditions in early development and adverse health outcomes in later life [20]. The main epigenetic mechanisms are DNA methylation and post-translational modifications of histone tails, as well as regulation by non-coding RNAs (microRNAs and long non-coding RNAs) [21].…”
Section: Conceptual Framework For Developmental Nutritional Programentioning
confidence: 99%
“…Among them, mechanisms of epigenetic regulation of gene activity seem to play a dominant role [38,39,40]. Inadequate nutritional environment during intrauterine development suppressed transcription of key genes regulating beta-cell development in rats [39].…”
Section: Evidence From Animal Modelsmentioning
confidence: 99%
“…Heijmans et al [33] had reported that preconception exposure to famine during the Dutch Hunger Winter was associated with lower methylation of the IGF2. And epigenetic dysregulation is associated with several components that contribute to type 2 diabetes risk, including altered feeding behavior, insulin secretion, and insulin action [34]. Moreover, there was animal evidence shows that malnutrition in fetal life might affect appetite, feeding behavior, and adiposity in adulthood [35].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, calorie restriction associated with maternal malnutrition has detrimental effects on the offspring. Research has established that low birth weight and maternal malnutrition are associated with insulin resistance in the key organs that control glucose homeostasis, establishing a direct association between maternal undernutrition and altered pancreatic β-cell function with the development of type 2 diabetes mellitus [49]. The possible involvement of deregulation in microRNA expression in the endocrine pancreas has been hypothesized as a mediator of early nutrition in the formation of β-cell mass and the subsequent risk of diabetes mellitus type 2 [50].…”
Section: Nutrition Conditionsmentioning
confidence: 99%